How do online community platforms and associated offline meetings support highly skilled (re-)migration? The case of the Rückkehrerstammtisch in Istanbul - Müller, Philip; König, Tobias (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
In this article we investigate online community platforms and associated offline meetings that cater to highly skilled (re-)migrants. To do so we draw on a case study of the Rückkehrerstammtisch in Istanbul, which is aimed especially at highly skilled (re-)migrants of Turkish origin, who have moved or plan to move from Germany to Turkey. The Rückkehrerstammtisch mainly consists of an online community platform on the professionally oriented social networking site Xing and regular offline community meetings in Istanbul. Based on a mixed-method case study approach using netnography and qualitative interviews, this article shows that the Rückkehrerstammtisch enables highly skilled persons of Turkish origin the access to migration related information and social networks that are often not available through their pre-existing family and friendship networks in Turkey. Our research thus contributes to the debate about social networks within the migration process of highly skilled persons.